Financial ratios' impact on stock prices in indonesian retail companies amid the covid-19 events in 2020–2022 - Yuliestia Dana, Intania Regina; Iskandar, Yusuf; Zaki, Achmad (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to assess the financial ratios of the stock prices of retail companies listed on the Indonesia Stock Exchange between 2020 and 2022 when the COVID-19 pandemic causes economic volatility. The financial ratios in this study include debt-to-equity ratio (DER), return on equity (ROE), and return on assets (ROA). The research methodology used is a quantitative approach using multiple regression analysis. Evaluate the relationship between debt-to-equity ratio (DER), return on equity (ROE), and return on assets (ROA) in stock prices. The second-party data came from the company's audited financial records and was analyzed using SPSS 27. The research findings show that return on assets (ROA) has a positive and significant impact on stock prices. This finding also indicates that companies have been efficient with their assets, which generates profits, which is an important factor in determining stock prices. Return on Equity (ROE) has a positive and significant impact on share price. This is evident from the fact that companies have used efficient asset disposal procedures during the COVID-19 pandemic, resulting in high profits that can contribute to an increase in stock prices. Debt to Equity Ratio (DER) has a significant negative effect on stock prices. It can be seen that companies can optimally manage their finances and silently create favorable financial conditions for the company. This can have an impact on increasing the company's share price. Simultaneously, Return on Equity (ROE), Return on Asset (ROA), and Debt to Equity Ratio (DER) have a significant influence on stock prices. This research can be applied to Return on Equity (ROE), Return on Asset (ROA), and Debt to Equity Ratio (DER) together affect the stock price of retail companies in Indonesia. This information can be useful for investors and financial management for the development of decisions in investment, and it is very important that financial analysis can be used as a guide when developing decisions in investment